LANGUAGE CHANGES AMONG JORDANIAN UNIVERSITY STUDENTS: WHATSAPP COMMUNICATION - Al Thunaibat , Marwan Mohammad; Sarjit Singh, Manvender Kaur (International Journal of Psychosocial Rehabilitation, 2025)
The internet communication language is a strange controversial language (Fenianos, 2020). This language includes many new linguistic changes or techniques. Also, the nature and the reasons of these techniques are still questionable. Thus, this study investigates linguistic changes appear through the communication of Jordanian university students on WhatsApp. After review literature, the study depends of focus group to collect data. The data are analyzing by the researcher qualitatively. The results of the study showed that students depend on their communication on six linguistic techniques. These techniques arecode-switching, abbreviations, leetspeak, emoticons, reduplication of letters, and rebus. Moreover, the reasons of using these techniques are revealed including using code switching to practice English, using abbrwviations and leetspeak for economic purpose, using emoticons and reduplication of letters to make the communication more real, and rebus for fun.